FACTORS CONTRIBUTING TO THE IMPLEMENTATION OF A WEB-BASED PARAGRAPH WRITING CLASS - Caecillia Devy Kurniawati (Indonesian JELT, 2012)
This study aims to see factors contributing to the implementation of a web-based Paragraph Writing class. The survey research design using open-ended questionnaire was implemented to find out the aspects, and based on the factors found from the questionnaire, an interview was developed to clarify how the factors really contributed to the students’ writing skills. The subjects were the English Letters Department students of Sanata Dharma University, Yogyakarta who were taking Paragraph Writing classes during the even semester academic year 2010/2011. The results show that there are twelve high factors and also one other factor contributing to the implementation of the web-based Paragraph Writing class.Keywords: paragraph writing, web-based learning